PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN : PERAN KOMISARIS INDEPENDEN DAN KOMITE AUDIT SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2019-2023) - Annisa Putri Nur Maharani; Nawangsari , Ajeng Tita (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study analyzes the influence of Corporate Social Responsibility (CSR) on firm value by examining the moderating role of Independent Commissioners and the Audit Committee. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2023 period using a purposive sampling method, resulting in a sample of 10 companies with 50 observations. Data analysis was conducted using multiple regression techniques with interaction variables. The results indicate that CSR has a positive and significant effect on firm value. Independent Commissioners were shown to strengthen the positive influence of CSR on firm value, while the Audit Committee did not show a significant moderating effect. These findings emphasize the importance of Independent Commissioners in optimizing the contribution of CSR to increasing firm value.